Present Status of Organizational Work–Life Balance Practices in Bangladesh: Employees Expectation and Organizational Arrangements - Hossen, Md. Miraj; Begum, Mareum; Zhixia, Chen (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
Work-Life Balance (WLB) or Work-Family Conflict (WFC) is one of the much talked issues in the modern business arena and all the stakeholder of business world such as- employers, employees, policy makers, academicians, consumers, and the common people are concerned about it. By considering the significances of the topic the researchers have taken an initiative to examine the present status of the WLB programs/ Employee friendly policies practices in the different organizations in Bangladesh through a designed questionnaire and interviewing the supervisors and employees of some selected organizations in multiple industries. Beside this the researchers also tries to explore what are the most wanted request comes from the employees, how the organizations respond against their requests, what perceptions bear the supervisor’s and the employee’s regarding WLB and what are the barriers may organization face to implement the WLB programs. The key findings of the research point out that most of the organizations in Bangladesh don’t have any formal policy to make work-life balance but they follow some informal approaches (flexibility in time, location, & schedule, leave provisions) to facilitates the employees WLB and make them relax, confident, committed and motivated towards their works to get satisfied employees and optimum HR productivity. The study concludes with mentioning some prospective outcomes of WLB which the organization may achieve by ensuring various WLB initiatives.